Analisis Kesulitan Membaca dan Menulis Siswa Kelas IV SD 2 Hadipolo - Syuroiya, Kamila Arodatus; Novitasari, Eva; Riswari, Lovika Ardana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
This study aims to describe the reading and writing difficulties of high-grade students and the factors that inhibit high-grade readers. The subjects in this study were 4th grade students, with a total of 30 students, 15 female students and 15 male students. In this study, the researcher focused on the difficulties of one student. In qualitative research, in the classroom, to find out the number of students who cannot read and write, only one student is interviewed using in-depth interview techniques. This technique involves interaction between the researcher and the research subject to gain an in-depth understanding of the subject's experiences and views related to literacy. The research was conducted at SD 2 Hadipolo. This research used qualitative methods with data collection using observation and interviews. The results of this study show that there is one student from the high school who has difficulty reading and writing. Factors causing the student's reading and writing difficulties include limitations in basic reading skills such as letter recognition, understanding letter sounds, distinguishing letters, or combining letters to make words. Students' lack of interest in learning letters, motivation to read, and lack of support from the surrounding environment, such as parents and teachers, can also be the cause of students' difficulties in reading.